Assessing the internal factor affecting the bank profitability in Indonesia: Case of dual banking system - Roisatun Kasanah; Achmad Fadlil Abidillah; Sulistya Rusgianto (Faculty of Economics, Universitas Islam Indonesia, 2022)
Purpose – In an uncertain economic condition, maintaining companies’ profitability is essential. This study aims to analyze and assess the factors that affect bank profitability by focusing on internal factors such as capital, size, asset quality, and liquidity risk. This study also observed the effect of Islamic and conventional banking in Indonesia with a comprehensive profitability analysis as measured by ROA, ROE, and NIM/NOM.Methodology – The method used in this research was panel data regression. The data studied were derived from the quarterly reports of Islamic and conventional banking in Indonesia for five years, from 2016 to 2020.Findings – The results showed that conventional banking in Indonesia had a higher level of profitability than Islamic banking. The profitability of conventional banks is significantly influenced by the level of equity, size, CKPN, and LDR. On the other hand, Islamic banking in Indonesia generally has a lower level of profitability, but in terms of individual performance, the value was not inferior to conventional banking. Variables that significantly influence the profitability of Islamic banking included equity, CKPN, and FDR.Implication – Banks in Indonesia must improve their performance so that the development of asset size can be in line with the level of profitability generated, maintain asset quality so that the health of the bank is maintained, and has proportional equity and LDR/FDR value.Originality – This research used three profitability ratios: ROA, ROE, and NIM/NOM, and analyzed Islamic and conventional banking, considering that Indonesia has a dual banking system, so the analysis carried out was more comprehensive.